EFFICACY OF ECO-FRIENDLY INSECTICIDES ON THE MANAGEMENT OF DIAMONDBACK MOTH (PLUTELLA XYLOSTELLA LINN.) ON CABBAGE - H.VANLALDIKI; SINGH , M. PREMJIT; P.K.SARKAR (The Bioscan, 2013)
Field experiment was conducted to study the relative efficacy of different eco-friendly insecticides comprising of four neem product (nimbecidine, agrineem, vijayneem and neemark), two Bt products (dipel and delfin), one entomopathogenic fungus, B.bassiana (biorin) and a chemical insecticide (nuvan) against diamondback moth (Plutella xylostella Linn.) vis-à-vis their effect on the predatory coccinellid, Coccinella s eptempunctata Linn. All the insecticides were superior in controlling the diamondback moth population in comparison to untreated control. Amongst the different treatments, Bt. (dipel) recorded the lowest larval population (0.21/plant) and proved to be the most effective treatment, followed by Bt (delfin) and nuvan with larval populations of 0.45 and 1.50/plant respectively, as against 8.88/plant in untreated control. Vijayneem was found to be the most inferior insecticide by recording the highest population of 3.06/plant. The mean yield ranged from 17.92 to 22.73t/ha in insecticidal treatments with the maximum yield in dipel as against 14.75t/ah in untreated control. Amongst all the tested compounds, agrineem and delfin proved to be the safest insecticide to the predatory beetle, Coccinella septempunctata with the highest population of 1.20/plant each against 1.28/plant in untreated control. The lowest beetle population (0.87/plant) was recorded in nuvan treated plots. However, all the insecticidal treatments were found to be safe to the predator as it was observed that there was no significant difference with untreated control after post applications counts.